Black Friday: Has the game changed?. Issue 4 (2nd October 2022) - Peters, Cara; Thomas, Jane
ABSTRACT: Previous research on Black Friday consumption rituals has focused on planning and shopping for an in-store customer experience. In recent times, however, consumer perceptions and shopping behaviors related to Black Friday have begun to shift. Consumers are shopping earlier, moving online, taking advantage of delivery and curbside pickup, and expecting retailers to provide a safe, socially distanced shopping experience. This study was grounded in theory from social change within the field of sociology. The purpose of this study was to examine how various factors, such as the pandemic, retailer strategies, online shopping, cultural trends are reshaping consumers' views and shopping behaviors related to Black Friday. Data were collected via 31 phenomenological interviews with consumers who have shopped on Black Friday in the past. Results were analyzed according to the protocol for phenomenology and were presented in the form of themes that emerged from the data. Overall, consumers believed that Black Friday had changed and had become less impactful. Changes were due to store policies and procedures around safety during the pandemic, retailers extending the number of days and weeks for Black Friday shopping, the convenience and breadth of products available among a plethora of online shopping alternatives, the impact of the economy on the ability to shop, and how the name Black Friday has negative associations for some shoppers. Managerial implications for retailers were discussed as the game of Black Friday has changed. Implications included strategies retailers can use to entice consumers as they try to revamp Black Friday and engage shoppers in the future.